Cardiolipin remodeling by ALCAT1 links mitochondrial dysfunction to Parkinson's diseases. Issue 3 (5th March 2019) - Song, Chengjie; Zhang, Jun; Qi, Shasha; Liu, Zhen; Zhang, Xiaoyang; Zheng, Yue; Andersen, John‐Paul; Zhang, Weiping; Strong, Randy; Martinez, Paul Anthony; Musi, Nicolas; Nie, Jia; et al.
Abstract: Cardiolipin (CL) is a mitochondrial signature phospholipid that is required for membrane structure, respiration, dynamics, and mitophagy. Oxidative damage of CL by reactive oxygen species is implicated in the pathogenesis of Parkinson's disease (PD), but the underlying cause remains elusive. This work investigated the role of ALCAT1, an acyltransferase that catalyzes pathological remodeling of CL in various aging‐related diseases, in a mouse model of PD induced by 1‐methyl‐4‐phenyl‐1, 2, 4, 6‐tetrahydropyridine (MPTP). We show that MPTP treatment caused oxidative stress, mtDNA mutations, and mitochondrial dysfunction in the midbrain. In contrast, ablation of the ALCAT1 gene or pharmacological inhibition of ALCAT1 prevented MPTP‐induced neurotoxicity, apoptosis, and motor deficits. ALCAT1 deficiency also mitigated mitochondrial dysfunction by modulating DRP1 translocation to the mitochondria. Moreover, pharmacological inhibition of ALCAT1 significantly improved mitophagy by promoting the recruitment of Parkin to dysfunctional mitochondria. Finally, ALCAT1 expression was upregulated by MPTP and by α‐synucleinopathy, a key hallmark of PD, whereas ALCAT1 deficiency prevented α‐synuclein oligomerization and S‐129 phosphorylation, implicating a key role of ALCAT1 in the etiology of mouse models of PD. Together, these findings identify ALCAT1 as a novel drug target for the treatment of PD. Abstract : Upregulation of ALCAT1 by MPTP‐induced α‐synucleinopathy and oxidative stress promotes cardiolipin peroxidation, leading to impaired mitochondrial fusion and mitophagy which trigger the onset of neurodegenerative diseases